Expired patents: An opportunity for higher education institutions - Mafu, Mhlambululi (Frontiers in Research Metrics and Analytics, 2023)
Patent protection typically lasts about 20 years from the filing date and is in exchange for sufficiently disclosing the invention. The disclosure aims to enrich technical knowledge globally, promote creativity and technological innovation and contribute to sustainable socio-economic development. After this protection period, the patent expires, and in principle, any person may begin practicing the specific subject matter previously protected by the patent. Since the invention originally met all the patentability requirements, it was disclosed sufficiently to stimulate further innovation by others through a thorough understanding of existing developments in the patent literature. Thus, in addition to scholarly research articles, this makes patents potentially valuable sources of technical information in research and academia, unlocking new technology opportunities. We use the exploratory research method to study a potentially genuine and vital research stream that uncovers the overlooked yet valuable scientific and technical information sources that higher education institutions could utilize to complement academic research articles. This work establishes a necessary research agenda that critically challenges researchers to tap into the immediately available and promising technology opportunities presented by patents in the public domain. Using case studies to gain in-depth, multi-faceted explorations about the impact of these patents, we find that technologies contained in expired patents, abandoned patents, and technologies not protected by IPRs, resulting in improved research quality and increased collaboration with industry, if adequately exploited and integrated with other technologies. Moreover, this could lead to increased academic patenting and commercialization with support from the university's Technology Transfer Office.